Nitschkia tectonae — a new ascomycete on teak from central India - VERMA, R.K. (Indian Phytopathology, 2010)
Nitschkia tectonae sp. nov. is described, illustrated and compared with allied taxa from India on dead stem of teak (Tectona grandis).